The impact of donor and recipient diabetes on renal transplant outcomes. Issue 12 (1st November 2020) - Singh, Navdeep; Washburn, Kenneth; Schenk, Austin; El‐Hinnawi, Ashraf; Bumgardner, Ginny; Logan, April; Rajab, Amer
Abstract: The use of diabetic kidneys is increasing worldwide with better outcome than being on waitlist and possible reversal of diabetic changes in transplanted kidneys. But particular caution is warranted in diabetic donor‐recipient combination. Total 1223 deceased donor kidney transplants were performed at our center between 2008 and 2018. 689 from non‐diabetic donor (NDD) to non‐diabetic recipient, 400 from non‐diabetic donor to diabetic recipient, 97 from diabetic to non‐diabetic recipient, and 32 from diabetic donor (DD) to diabetic recipient. The DD was older than NDDs (median age 48 vs 39 years, P  < 0.0001). DD had higher BMI (35.6 vs 26.9, P  < 0.0001), higher KDPI (74% vs 37%, P  < 0.0001), and higher terminal creatinine (1.10 mg/dl vs 0.95 mg/dl, p 0.0046) than the NDD. Diabetes recipients were comparatively older (57 vs 54, P  < 0.001). DD recipients had higher serum creatinine at 6 months (1.70 vs 1.50 mg/dl, p 0.00304) and 2 years post‐transplant (1.70 vs 1.50 mg/dl P  < 0.0002). DD recipients had more favorable end CPRA than NDD recipients (77.5% at 0% vs 67.4% at 0, P  = 0.0074). Ten‐year patient and graft survival was best in NDD‐recipient pair and worse in DD‐recipient pair. Diabetic donor kidneys to diabetic recipients have lower 1‐, 3‐, and 5‐year graft survival.